Nuclear medicine in pharmaceutical research - Frier, M. (Malcolm); Perkins, A. C.; ebrary, Inc. (London ; Philadelphia : Taylor & Francis, 1999)
"This book defines the role and scope of nuclear medicine imaging techniques (gamma scintigraphy) in pharmaceutical research, giving a wealth of information from clinical trial data. No other technique can localize so precisely the site of disintegration of a tablet in the GI tract, the penetration of an aerosol in the lung or the residence time of a drug on the cornea." "Nuclear Medicine in Pharmaceutical Research will be a valuable resource to all with interests in drug delivery, whether working in pharmaceutical research, academia or clinical sciences."
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nuclear medicine -- Methodology; Radioisotope scanning; Electronic books